2019
DOI: 10.30574/gscbps.2019.7.2.0079
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of vitamin E and grape seed oil against acute hepatorenal ivermectin toxicity in mice: biochemical and histopathological studies

Abstract: Ivermectin (IVM), a broad spectrum anthelmintic drug, is considered a safe drug; however, there are few reports about its toxic effects in particularly at accidental overdose exposure. Therefore, the current study was designed to investigate the potential protective roles of vitamin E (Vit E) and grape seed oil (GSO) against the acute hepatorenal toxicity of IVM in mice. Mice were divided into four equal groups. Control vehicle group was administrated corn oil (0.2 ml/animal), IVM group was administrated IVM (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The evaluation of serum creatinine and the blood urea levels post-administration of drugs provides a good overview for nephrotoxicity analysis [ 46 ]. Various studies conducted on avermectins (mainly the ivermectin and the abamectin) have proven these drugs to induce nephrotoxicity in many animals like mice, bats, rabbits, and rats [ 28 , 34 , 53 , 54 , 55 , 56 ]. The main molecular mechanism through which avermectins exert their nephrotoxic effect is the lipid peroxidation which results from the action of reactive oxygen species [ 51 ].…”
Section: Avermectinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of serum creatinine and the blood urea levels post-administration of drugs provides a good overview for nephrotoxicity analysis [ 46 ]. Various studies conducted on avermectins (mainly the ivermectin and the abamectin) have proven these drugs to induce nephrotoxicity in many animals like mice, bats, rabbits, and rats [ 28 , 34 , 53 , 54 , 55 , 56 ]. The main molecular mechanism through which avermectins exert their nephrotoxic effect is the lipid peroxidation which results from the action of reactive oxygen species [ 51 ].…”
Section: Avermectinsmentioning
confidence: 99%
“…Various studies have also indicated the avermectins to have toxic effects on animals [ 26 , 27 , 28 , 29 ]. For example, collie dogs experiencing severe illness presented to the clinic were found to be suffering from ivermectin toxicity [ 30 ].…”
Section: Introductionmentioning
confidence: 99%